Modified ferritin, cross-linked ferritin and preparation method and application of modified ferritin and cross-linked ferritin

Crosslinked ferritin obtained through genetic modification or chemical modification is used for subcutaneous and tissue filling, solving the problems of limited support and easy degradation of existing filling materials, achieving longer filling effects and better biocompatibility.

CN119708190APending Publication Date: 2025-03-28SHANGHAI SHANGZEYONGZHI BIOTECHNOLOGY PARTNERSHIP (LLP)
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411361290.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2024-09-14
Filing Date
2024-09-27
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

Existing dermal filling materials such as hyaluronic acid and collagen have limited support and are easy to degrade, resulting in short filling effect, requiring frequent injections, and a short retention time in the body.

Method used

Crosslinked ferritin obtained through genetic modification or chemical modification forms a cage-shaped multimeric structure, which has good biocompatibility and anti-degradability, and is used for subcutaneous and tissue filling.

Benefits of technology

Crosslinked ferritin has excellent support, anti-degradability and elasticity, can maintain the filling effect for a long time, reduce the injection frequency, and remain stable in the body.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119708190A_ABST
    Figure CN119708190A_ABST
Patent Text Reader

Abstract

The invention discloses modified ferritin, cross-linked ferritin as well as a preparation method and application of the modified ferritin and the cross-linked ferritin. The modified ferritin comprises a plurality of light chain subunits or heavy chain subunits of ferritin of natural origin wherein the plurality of light chain subunits or the plurality of heavy chain subunits form a multimer, preferably a cage multimer. The cross-linked ferritin is ferritin of a natural source or a variant of the ferritin, or is cross-linked ferritin formed by cross-linking modified ferritin. The cross-linked ferritin still keeps the unique cage-shaped structure of ferritin, has the characteristics of good elasticity, high support degree, small swelling degree, degradation resistance and the like, and can realize better subcutaneous and tissue filling effects.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] This application claims the priority of Chinese Patent Application No. 2023112753858 filed on September 28, 2023 and the priority of Chinese Patent Application No. 2024112962839 filed on September 14, 2024. This application cites the full text of the above Chinese patent application. Technical Field

[0002] The invention belongs to the technical field of biomedical materials, and in particular relates to modified ferritin, cross-linked ferritin, and a preparation method and application thereof. Background Art

[0003] The skin is the largest organ in the human body and plays an important role in resisting external damage and maintaining the stability of the internal environment. As we age, skin aging will cause facial tissue sagging and wrinkles. Subcutaneous filling can effectively reduce facial sagging, supplement volume loss, reshape facial contours, and improve skin quality. Local injection of hyaluronic acid and / or collagen has the advantages of simple operation, less damage, and good biocompatibility, and has become a commonly used method.

[0004] Hyaluronic acid, also known as hyaluronic acid, has the advantages of good tissue compatibility, easy injection, immediate effect after filling injection, and minimally invasive. It is one of the most commonly used skin fillers in clinical practice. Since hyaluronic acid is an acidic mucopolysaccharide, it cannot form a three-dimensional spatial structure after cross-linking, and the support after filling is limited. It is also prone to the Tyndall phenomenon, which affects the appearance after filling. Hyaluronic acid is a high molecular polymer. Its chemical structure contains hydroxyl and carboxyl groups. It is easy to hydrolyze in the body after interacting with water. Biological enzymes (especially hyaluronidase and human free radicals) have a strong degradation effect on hyaluronic acid. Therefore, hyaluronic acid has a short retention time in the body and requires repeated injections to achieve the effect. At the same time, skin cells absorb hyaluronic acid very quickly after the first injection, and staying up late and drinking alcohol will accelerate the metabolism of hyaluronic acid in the body. The metabolism rate of hyaluronic acid in areas with frequent activities will also be accelerated. Hyaluronic acid subcutaneous filling generally lasts for 6-8 months. At the same time, collisions can easily cause displacement and morphological changes of hyaluronic acid. Therefore, hyaluronic acid still has some defects as a subcutaneous filling material and needs further product improvement.

[0005] Collagen is another common filler material, which has the advantages of good tissue compatibility, easy injection, immediate effect after filling injection, and minimally invasive. The natural collagen in human skin is type I collagen, and the amino acid sequence of this collagen contains 3 uncommon amino acids: 4-hydroxyproline (9%), 3-hydroxyproline (0.1%) and 5-hydroxylysine (0.6%). Through amino acid modification, it can form a stable covalent bond connection, further forming a right-handed triple helix protocollagen molecule (protocollagen), and each strand of the protocollagen molecule is a left-handed helix. Therefore, the natural collagen in the skin has strong support and tensile strength. The subcutaneous filler collagen currently used in the market is mostly collagen fragments expressed by prokaryotes, which cannot form left-handed helical single chains or right-handed triple helices. Therefore, it lacks the strong support and tensile strength of collagen in the body and cannot play its true function. At the same time, because the filler is a collagen fragment, it is easily hydrolyzed by collagenase in the body and has a short retention time in the body.

[0006] In view of the shortcomings of hyaluronic acid and collagen, such as limited supporting capacity and easy degradation, there is an urgent need to develop new filling materials that are long-lasting, have better biomechanical support, and can be produced on a large scale industrially.

[0007] Ferritin is a hollow spherical protein naturally found in animals, with an inner diameter of 8nm and an outer diameter of 12nm. It is a 24-mer protein cage structure formed by self-assembly of light chain subunits and heavy chain subunits. In current research, ferritin is often used in tissue engineering or as a delivery carrier for small molecule drugs, biological agents, nucleic acids, etc., and there are few reports on its use in the preparation of filling materials. Summary of the invention

[0008] In order to solve the above-mentioned defects existing in the prior art, the present invention provides modified ferritin, cross-linked ferritin, preparation method and application; the prepared cross-linked ferritin has good biocompatibility, and in practical application, has excellent support, degradation resistance, elasticity and other properties.

[0009] To achieve the above purpose, the technical solution adopted by the present invention is as follows:

[0010] The present invention provides a modified ferritin, which comprises a plurality of light chain subunits or heavy chain subunits of ferritin from natural sources, wherein the plurality of light chain subunits or the plurality of heavy chain subunits form a multimer; preferably a cage-shaped multimer.

[0011] In the present invention, "modified ferritin" means ferritin of non-natural origin, for example, artificial ferritin obtained by genetically modifying ferritin of natural origin. In the present invention, the amino acid sequence of the light chain subunit may be as shown in SEQ ID NO: 1 or have at least 80% identity with the sequence shown in SEQ ID NO: 1, preferably at least 85%, 90%, 95%, 96%, 97%, 98% or 99% identity.

[0012] In the present invention, the amino acid sequence of the heavy chain subunit may be as shown in SEQ ID NO: 2, 6 or 7 or have at least 80% identity with the sequence shown in SEQ ID NO: 2, 6 or 7, preferably at least 85%, 90%, 95%, 96%, 97%, 98% or 99% identity.

[0013] In some embodiments, the modified ferritin comprises 8, 16, 24, or 48 light chain subunits or 8, 16, 24, or 48 heavy chain subunits.

[0014] In some embodiments, the natural source includes animal, plant, fungal or bacterial sources, preferably animal sources; the animal is a vertebrate, preferably a mammal, more preferably a human.

[0015] In some preferred embodiments, the modified ferritin is composed of 24 light chain subunits forming a cage-shaped multimer, or is composed of 24 heavy chain subunits forming a cage-shaped multimer.

[0016] The present invention also provides a cross-linked ferritin; it is a cross-linked ferritin formed by cross-linking ferritin from a natural source or a variant thereof, and the cross-linked ferritin retains the multimeric structure of the ferritin from the natural source or a variant thereof; or it is a cross-linked ferritin formed by cross-linking the modified ferritin as described above, and the cross-linked ferritin retains the multimeric structure of the modified ferritin; wherein the variant has at least 80% identity with the amino acid sequence of the ferritin from the natural source, preferably at least 85%, 90%, 95%, 96%, 97%, 98% or 99% identity.

[0017] Preferably, the cross-linked ferritin is in the form of a hydrogel or microsphere structure.

[0018] In the present invention, the swelling degree of the cross-linked ferritin may be lower than 1000%, preferably lower than 600%, and more preferably lower than 500%.

[0019] In the present invention, the elastic modulus of the cross-linked ferritin may be higher than 100 Pa, preferably higher than 600 Pa, and more preferably higher than 1000 Pa.

[0020] In the present invention, the viscosity modulus of the cross-linked ferritin may be higher than 10Pa, preferably higher than 30Pa, more preferably higher than 50Pa, and even more preferably higher than 100Pa.

[0021] In the present invention, the natural ferritin may be derived from animals, plants, fungi or bacteria, preferably animals; the animal is a vertebrate, preferably a mammal, and more preferably a human.

[0022] Preferably, the cross-linking is performed by a biological cross-linking reaction or a chemical cross-linking reaction.

[0023] In some embodiments, the ferritin is mouse heavy chain ferritin, preferably with the amino acid sequence of NCBI accession number NP_034369.1.

[0024] In some embodiments, the ferritin is mouse light chain ferritin, preferably with an amino acid sequence having an NCBI accession number of AAA37614.1.

[0025] In some embodiments, the ferritin is Drosophila melanogaster heavy chain ferritin, preferably, the NCBI accession number of its amino acid sequence is NP_001247366.1.

[0026] In some embodiments, the ferritin is Drosophila melanogaster light chain ferritin, preferably, the NCBI accession number of its amino acid sequence is NP_001263105.1.

[0027] In some embodiments, the ferritin is Caenorhabditis elegans ferritin, preferably, the NCBI accession number of its amino acid sequence is NP_491198.1.

[0028] In some embodiments, the ferritin is oyster ferritin, preferably with an amino acid sequence as shown in SEQ ID NO:3.

[0029] In some embodiments, the ferritin is human mitochondrial ferritin, preferably, the NCBI accession number of its amino acid sequence is NC_000005.10.

[0030] In some embodiments, the ferritin is soybean ferritin, and preferably the NCBI accession number of its amino acid sequence is NP_001236534.2.

[0031] In some embodiments, the ferritin is Arabidopsis ferritin, preferably the NCBI accession number of its amino acid sequence is NP_195780.1.

[0032] In some embodiments, the ferritin is beet chloroplast ferritin, preferably, the NCBI accession number of its amino acid sequence is XP_010676813.1.

[0033] In some embodiments, the ferritin is Mucor microsporum ferritin, and preferably the NCBI accession number of its amino acid sequence is XP_023465511.1.

[0034] In some embodiments, the ferritin is encephalitogenic microsporidia ferritin, and preferably the NCBI accession number of its amino acid sequence is XP_003887486.1.

[0035] In some embodiments, the ferritin is a non-heme ferritin, preferably a non-heme ferritin of the Enterobacteriaceae family, and more preferably the NCBI accession number of its amino acid sequence is WP_000917208.1.

[0036] In some embodiments, the ferritin is Acinetobacter ferritin, preferably, the NCBI accession number of its amino acid sequence is WP_002117082.1.

[0037] In some embodiments, the ferritin is Campylobacter ferritin, preferably with the amino acid sequence of NCBI accession number WP_002786063.1.

[0038] In some embodiments, the ferritin is a Bacteroides ferritin, preferably with the amino acid sequence of NCBI accession number WP_010538613.1.

[0039] In some embodiments, the ferritin is Pseudomonas aeruginosa ferritin, preferably with an amino acid sequence as shown in SEQ ID NO:4.

[0040] In some embodiments, the ferritin is Pyrococcus aerophilus ferritin, and preferably the NCBI accession number of its amino acid sequence is NC_014804.1.

[0041] In some embodiments, the ferritin is Pyrococcus jacobinii ferritin, and preferably the NCBI accession number of its amino acid sequence is NC_015680.1.

[0042] In some embodiments, the ferritin is Deinococcus-Thermus ferritin, and preferably the NCBI accession number of its amino acid sequence is WP_038069286.1.

[0043] In some embodiments, the ferritin is actinomycete ferritin, and preferably the NCBI accession number of its amino acid sequence is NP_218358.1.

[0044] In some embodiments, the ferritin is a Proteobacteria ferritin, and preferably the NCBI accession number of its amino acid sequence is NP_417795.1.

[0045] In some embodiments, the ferritin is Escherichia coli ferritin, preferably with an amino acid sequence as shown in SEQ ID NO:5.

[0046] In some embodiments, the ferritin is an Archaeota ferritin, and preferably the NCBI accession number of its amino acid sequence is WP_012309233.1.

[0047] In some embodiments, the ferritin is Pyrococcus furiosus ferritin, preferably, the NCBI accession number of its amino acid sequence is WP_011011871.1.

[0048] In some embodiments, the ferritin is Methanosarcina ferritin, preferably, the NCBI accession number of its amino acid sequence is WP_048037772.1.

[0049] In some embodiments, the cross-linked ferritin further comprises hyaluronic acid and / or collagen.

[0050] Preferably, the volume ratio of the cross-linked ferritin to the hyaluronic acid is 1:5-5:1.

[0051] Preferably, the volume ratio of the cross-linked ferritin to the collagen is 1:5-5:1.

[0052] Preferably, the molar concentration ratio or mass ratio of the cross-linked ferritin to the hyaluronic acid is 1:5-5:1.

[0053] Preferably, the molar concentration ratio or mass ratio of the cross-linked ferritin to the collagen is 1:5-5:1.

[0054] The present invention also provides a method for preparing the cross-linked ferritin as described above, the method comprising the following steps:

[0055] The naturally derived ferritin or its variants, or the modified ferritin as described above, is made into cross-linked ferritin through a cross-linking reaction; the cross-linking reaction is a chemical cross-linking reaction or a biological cross-linking reaction.

[0056] In the present invention, when the cross-linking reaction is a chemical cross-linking reaction, the cross-linking reaction may include the following steps: mixing a neutral solution containing ferritin from a natural source or a variant thereof, or a neutral solution containing the modified ferritin as described above with a cross-linking agent, and performing a cross-linking reaction to obtain the product.

[0057] Wherein, after the cross-linking reaction, hyaluronic acid and / or collagen may be mixed into the ferritin hydrogel.

[0058] Wherein, the cross-linking reaction may further include neutralization, washing and / or homogenization.

[0059] Among them, the cross-linking agent can be selected from one or more of 1,4-butanediol diglycidyl ether (BDDE), genipin (GP), 1-ethyl-(3-dimethylaminopropyl) carbodiimide hydrochloride (EDC), N-hydroxysuccinimide (NHS), nordihydroguaiaretic acid (NDGA) and glutaraldehyde, preferably 1,4-butanediol diglycidyl ether (BDDE).

[0060] The volume percentage of the cross-linking agent relative to the neutral solution may be 3-30%, preferably 6%.

[0061] The cross-linking reaction may be carried out in a constant temperature water bath; the temperature of the cross-linking reaction may be 60-72° C., such as 60° C.; and the time of the cross-linking reaction may be 20-150 min.

[0062] Wherein, the pH of the neutral cross-linked ferritin solution may be 8.

[0063] The concentration of the naturally derived ferritin or its variant, or the modified ferritin as described above may be 10-600 mg / mL, preferably 50-300 mg / mL, such as 100 mg / mL.

[0064] Wherein, the neutralization may include pickling to neutrality; the pickling preferably includes leaching with an acidic agent; preferably, the acidic agent is selected from one or more of hydrochloric acid, sulfuric acid and acetic acid, such as acetic acid.

[0065] Wherein, the cleaning may include cleaning with a buffered saline solution; preferably, the buffered saline solution is selected from one or more of phosphate buffer, saline, Tris-HCl buffer and HEPES, such as saline; preferably, the concentration of the buffered saline solution is 10-100 mM and the pH is 6-8.

[0066] The cleaning time may be 12-30 hours, for example 24 hours.

[0067] In the present invention, when the cross-linking reaction is a biological cross-linking reaction, the naturally derived ferritin can be cross-linked via disulfide bonds; preferably, the naturally derived ferritin is fused and expressed with a cysteine-containing polypeptide by genetic engineering to obtain cross-linked ferritin.

[0068] Preferably, the natural source includes animal, plant, fungal or bacterial sources, preferably animal sources; the animal is a vertebrate, preferably a mammal, and more preferably a human.

[0069] In a specific embodiment, the biological cross-linking reaction includes, for example, mixing ferritin modified with a cysteine-containing polypeptide and β-mercaptoethanol, magnetically stirring, and after a preliminary reaction, centrifuging to remove the supernatant, washing the protein precipitate with PBS, and then dissolving it in a DMSO solution (pH 3-8), and magnetically stirring until the reaction is complete.

[0070] The present invention also provides a naturally derived ferritin or a variant thereof, or a use of the modified ferritin as described above in the preparation of a subcutaneous or tissue filler; wherein the variant has at least 80% identity with the amino acid sequence of the naturally derived ferritin, preferably at least 85%, 90%, 95%, 96%, 97%, 98% or 99% identity.

[0071] On the basis of being in accordance with the common sense in the art, the above-mentioned preferred conditions can be arbitrarily combined to obtain the preferred embodiments of the present invention.

[0072] The reagents and raw materials used in the present invention are commercially available.

[0073] The positive and progressive effects of the present invention are:

[0074] The present invention is the first to use cross-linked ferritin obtained by cross-linking ferritin from natural sources or its variants, or modified ferritin for subcutaneous and tissue filling. Compared with the raw materials of existing filling materials, the ferritin of the present application, especially the ferritin obtained by genetic modification, has good biocompatibility and non-immunogenicity. The cross-linked ferritin still maintains the unique complete polymer structure (cage structure) of ferritin, and has the characteristics of good elasticity, high support, low swelling, anti-degradation, not easy to shift, long retention time in the body, and injectable use, which can achieve better subcutaneous and tissue filling effects. BRIEF DESCRIPTION OF THE DRAWINGS

[0075] Figure 1 and Figure 2 The microscopic morphology characterization results of the hydrogels obtained in Examples 1-2 and Comparative Examples 1-4.

[0076] Figure 3 Microscopic morphological characterization results of the hydrogels obtained in Example 1 and Examples 10-15 after being diluted 100 times.

[0077] Figure 4 The results show the anti-enzymatic ability of uncross-linked LFn, HFn, BSA and Col at 25℃.

[0078] Figure 5 The results of enzymatic hydrolysis rate characterization at 37°C of the hydrogels obtained in Examples 1-2 (LFn, HFn), commercial HA, commercial Col, and the hydrogels obtained in Examples 10-13 (LFn-HA, HFn-HA, LFn-Col, and HFn-Col).

[0079] Figure 6 It is the swelling level of the hydrogels obtained in Examples 1-2 and Comparative Examples 3-4 after immersion for 24 hours.

[0080] Figure 7 It is the swelling degree of the hydrogel obtained in Examples 1-2 and Comparative Examples 3-4 after immersion for 24 hours.

[0081] Figure 8 The elastic and viscous moduli of the hydrogels obtained in Examples 1-2 and Comparative Examples 3-4.

[0082] Fig. 9 and Fig.10 The gel spot volume and displacement level of the hydrogels obtained in Examples 1-2 and Comparative Examples 3-4 after subcutaneous injection.

[0083] Fig.11 The results of gel point maintenance after subcutaneous injection of the hydrogels obtained in Examples 1-2 and Comparative Examples 3-4 are shown.

[0084] Fig.12 These are the inflammatory factor detection results of the hydrogels obtained in Examples 1-2 and Comparative Examples 3-4 after subcutaneous injection. DETAILED DESCRIPTION

[0085] The following will be described in detail with reference to the accompanying drawings. The following examples are only used to more clearly illustrate the technical solution of the present invention, and are therefore only used as examples, and cannot be used to limit the scope of protection of the present invention. It should be noted that, unless otherwise specified, the technical terms or scientific terms used in this application should be the usual meanings understood by those skilled in the art to which the present invention belongs. The reagents used in the examples are all commercially available conventional products unless otherwise specified.

[0086] definition

[0087] Ferritin is a common cage-shaped self-assembling protein that is widely present in animals, plants and microorganisms. Its main function is to convert toxic divalent iron into trivalent iron and store it in the internal cavity to regulate the iron metabolism balance of the organism.

[0088] The ferritin of the present invention refers to any ferritin that can form a ring or cage structure, which can be a ferritin of natural origin or a modified ferritin, such as a recombinantly expressed ferritin, or a variant thereof; it can be derived from prokaryotes, protozoa, fungi, plants or animals, such as dry bacteria, fungi, insects, reptiles, birds, amphibians, fish, mammals; for example, rodents, ruminants, non-human primates or humans; such as mice, rats, guinea pigs, dogs, cats, horses, sheep, monkeys, gorillas, and humans. From bacteria to humans, although the ferritin amino acid sequences of different organisms are very different, their structures are similar and can form a ring or cage protein shell structure.

[0089] In some embodiments or comparative examples, a neutral / alkaline crosslinking method is used to prepare a hydrogel: 6% of the crosslinking agent BDDE is taken by volume and slowly added to the protein solution. When observed against light, it can be seen that the crosslinking agent slowly sinks to the bottom or suspends in a filamentous state and separates from the protein solution. The gun tip is suspended at the solution separation point, and the solution is blown slowly and gently, and observed against light until the separation and suspension disappear completely, indicating that the solution is fully mixed. The solution is then crosslinked in a water bath at 60-72°C for 20-150 minutes.

[0090] In some embodiments or comparative examples, a biocrosslinking method is also used to prepare the hydrogel: the gene sequence of the ferritin subunit is fused with the peptide chain by genetic engineering to obtain ferritin with a polypeptide connected to the outer surface; then the ferritin solution (1 mg / mL, the solvent is 20mM Tris-HCl), β-mercaptoethanol (β-ME) is added dropwise to a working concentration of 20mmol / L, and magnetic stirring is performed for 10 minutes. The reaction solution is collected, centrifuged for 10 minutes, the supernatant is removed, and the protein precipitate is washed twice with PBS. The collected protein precipitate is dissolved in a 6% concentration of DMSO solution (pH 3-8), the protein solution concentration is 2mg / mL, and magnetic stirring is performed until the reaction is complete. Wherein, the polypeptide here can be any polypeptide chain containing cysteine.

[0091] The amino acid sequence of ferritin used in the examples or comparative examples of the present invention may be specifically as follows:

[0092] 1. Human light chain ferritin:

[0093] SSQIRQNYSTDVEAAVNSLVNLYLQASYTYLSLGFYFDRDDVALEGVSHFFRELAEEKREGYERLLKMQNQRGGRALFQDIKKPAEDEWGKTPDAMKAAMALEKKLNQALLDLHALGSARTDPHLCDFLETHFLDEEVKLIKKMGDHLTNLHRLGGPEAGLGEYLFERLTLKHD[SEQ ID NO:1];

[0094] 2. Human heavy chain ferritin-1:

[0095] MTTASTSQVRQNYHQDSEAAINRQINLELYASYVYLSMSYYFDDDVALKNFAKYFLHQSHEEREHAEKLMKLQNQRGGRIFLQDIKKPDCDDWESGLNAMECALHLEKNVNQSLLELHKLATDKNDPHLCDFIETHYLNEQVKAIKELGDHVTNLRKMGAPESGLAEYLFDKHTLGDSDNES[SEQ ID NO:2];

[0096] 3. Mouse heavy chain ferritin—NCBI Reference Sequence: NP_034369.1;

[0097] 4. Mouse light chain ferritin—GenBank: AAA37614.1;

[0098] 5. Drosophila melanogaster heavy chain ferritin—NCBI Reference Sequence: NP_001247366.1;

[0099] 6. Drosophila melanogaster light chain ferritin—NCBI Reference Sequence: NP_001263105.1

[0100] 7. Caenorhabditis elegans ferritin—NCBI Reference Sequence: NP_491198.1;

[0101] 8. Oyster ferritin (PDB:6LIJ):

[0102] MAESQCRQNYHQESEAGINRQINMELYACYTYQSMAYYFDRDDVALPGFSKFFKNSSDEEREHAEKLMKYQNKRGGRVVLQDIKKPDRDEWGTGLDAMQVALQLEKTVNQSLLDLHKVADSHQDAQMCDFLETHYLEEQVNAIKEISDHITQLKRVGSGLGEYEYDRRLDS*[SEQ ID NO:3];

[0103] 9. Human mitochondrial ferritin—NCBI Reference Sequence: NC_000005.10;

[0104] 10. Soybean ferritin—NCBI Reference Sequence: NP_001236534.2;

[0105] 11. Arabidopsis ferritin 1—NCBI Reference Sequence: NP_195780.1;

[0106] 12. Sugar beet chloroplast ferritin—NCBI Reference Sequence: XP_010676813.1;

[0107] 13. Mucor microsporidial ferritin—NCBI Reference Sequence: XP_023465511.1;

[0108] 14. Encephalitogenic microsporidium ferritin—NCBI Reference Sequence: XP_003887486.1;

[0109] 15. Non-heme iron protein of Enterobacteriaceae—NCBI Reference Sequence: WP_000917208.1;

[0110] 16. Acinetobacter bacterial ferritin—NCBI Reference Sequence: WP_002117082.1;

[0111] 17. Campylobacter ferritin—NCBI Reference Sequence: WP_002786063.1;

[0112] 18. Bacteroides ferritin—NCBI Reference Sequence: WP_010538613.1;

[0113] 19. Pseudomonas aeruginosa ferritin (PDB: 6NLF):

[0114] MKGDKKVIQHLNKILGNELIAINQYFLHSRMWNDWGLKRLGAHEYHESIDEMK HADKLIERILFLEGLPNLQDLGKLLIGENTQEMLQCDLNLELKATKDLREAIVHCEQVH DYVSRDLLKDILESEEEHIDYLETQLGLIQKVGLENYLQSHMHEDD*[SEQ ID NO:4];

[0115] 20. Thermococcus aerophilus ferritin—NCBI Reference Sequence: NC_014804.1;

[0116] 21. Pyrococcus jacobinii ferritin—NCBI Reference Sequence: NC_015680.1;

[0117] 22. Ferritin from Deinococcus-Thermus phylum—NCBI Reference Sequence: WP_038069286.1;

[0118] 23. Actinomycete ferritin—NCBI Reference Sequence: NP_218358.1;

[0119] 24. Proteobacteria ferritin—NCBI Reference Sequence: NP_417795.1;

[0120] 25. Escherichia coli ferritin:

[0121] MLKPEMIEKLNEQMNLELYSSLLYQQMSAWCSYHTFEGAAAFLRRHAQEEMTH MQRLFDYLTDTGNLPRINTVESPFAEYSSLDELFQETYKHEQLITQKINELAHAAMTNQ DYPTFNFLQWYVSEQHEEEKLFKSIIDKLSLAGKSGEGLYFIDKELSTLDTQN[SEQ ID NO:5];

[0122] 26. Archaea ferritin—NCBI Reference Sequence: WP_012309233.1;

[0123] 27. Pyrococcus furiosus ferritin—NCBI Reference Sequence: WP_011011871.1;

[0124] 28. Methanosarcina ferritin—NCBI Reference Sequence: WP_048037772.1;

[0125] 29. Human heavy chain ferritin-2:

[0126] MTTASTSQVRQNYHQDSEAAINRQINLELYASYVYLSMSYYFDDRDDVALKNFAKYFLHQSHEEREHAEKLMKLQNQRGGRIFLQDIKKPDCDWESGLNAMECALHLEKNVNQSLLELHKLATDKNDPHLCDFIETHYLIKELGDHVTNLRKMGAPESGLAEYLFDKHTLGDSDNES[SEQ ID NO:6];

[0127] 30. Human heavy chain ferritin-3:

[0128] MTTASTSQVRQNYHQDSEAAINRQINLELYASYVYLSMSYYFDDRDDVALKNFAKYFLHQSHEEREHAEKLMKLQNQRGGRIFLQDIKKPDCDWESGLNAMECALHLEKNVNQSLLELHKLATDKNDPHLCDFIETHYLIKELGCHVTNLRKMGAPESGLAEYLFDKHTLGDSDNES[SEQ ID NO:7].

[0129] Example 1

[0130] The ferritin used in this example is modified human ferritin (human light chain ferritin, LFn), which contains 24 light chain subunits, and the amino acid sequence of each subunit is shown in SEQ ID NO:1.

[0131] The specific preparation steps of human light chain ferritin (LFn) hydrogel are as follows:

[0132] 1,4-Butanediol diglycidyl ether (BDDE) was added to a 200 mg / mL LFn aqueous solution with a pH value of 8 at a volume percentage of 6%, mixed evenly, and placed in a constant temperature water bath, the reaction temperature was set to 60°C, and the reaction time was 20-150 min to obtain a chemically cross-linked LFn protein gel. The cross-linked LFn protein gel was then washed with 0.05M acetic acid to a pH of 7, washed with physiological saline for 24 hours, homogenized, and encapsulated to obtain a chemically cross-linked LFn hydrogel (neutral cross-linking).

[0133] Example 2

[0134] The ferritin used in this example is a modified human ferritin (human heavy chain ferritin, HFn), which contains 24 subunits, and the amino acid sequence of each subunit is shown in SEQ ID NO:2.

[0135] According to the same method as in Example 1, chemically cross-linked HFn hydrogel (neutral cross-linking) was prepared under neutral conditions.

[0136] Example 3-Example 9

[0137] The packaged LFn protein solution was placed in the sample chamber of the freeze dryer, and after pre-freezing, sublimation drying, and analytical drying, the freeze-dried LFn protein was obtained. According to the ratio shown in Table 1, the LFn freeze-dried protein was weighed and added to 1 mL of BDDE pH 8 aqueous solution, respectively, and mixed evenly and placed in a constant temperature water bath, the reaction temperature was set to 60°C, and the reaction time was 20-150 min to obtain different chemically cross-linked LFn protein gels.

[0138] Then the cross-linked LFn protein gel was neutralized to pH 7 by immersion in 0.05 M acetic acid, washed with physiological saline for 24 h, homogenized, and sealed.

[0139] Table 1

[0140] serial number Weight of LFn freeze-dried protein (mg) Volume percentage of BDDE aqueous solution (%) Example 3 300 3 Example 4 300 6 Example 5 300 9 Example 6 400 6 Example 7 550 3 Example 8 550 6 Example 9 550 9

[0141] Example 10

[0142] The ferritin used in this example is modified human ferritin (human light chain ferritin, LFn), which contains 24 subunits, and the amino acid sequence of each subunit is shown in SEQ ID NO:1.

[0143] Add 50 mg of hyaluronic acid (HA, molecular weight: 200KD) to 200 mg / mL LFn solution with a pH value of 8, and gradually stir and dissolve at room temperature. Add BDDE to the mixed solution of LFn and HA at a volume percentage of 6%. After stirring evenly, place it in a 60°C constant temperature water bath for reaction for 1 to 1.5 hours to obtain a gel of LFn chemically cross-linked HA, hereinafter referred to as LFn-HA. Then, the gel is neutralized with 0.5% HAC to a pH of 7, washed with physiological saline for 15 hours, homogenized, and potted.

[0144] Embodiment 11

[0145] The ferritin used in this example is modified human ferritin (human heavy chain ferritin, HFn), which contains 24 subunits, and the amino acid sequence of each subunit is shown in SEQ ID NO:2.

[0146] 50 mg of hyaluronic acid (HA, molecular weight: 200KD) was added to a 200 mg / mL HFn solution with a pH value of 8, and gradually stirred and dissolved at room temperature. BDDE was added to the mixed solution of HFn and HA at a volume percentage of 6%. After stirring evenly, it was placed in a 60°C constant temperature water bath for reaction for 1 to 1.5 hours to obtain a HFn chemically cross-linked HA gel, hereinafter referred to as HFn-HA. The gel was then washed with 0.5% HAC to neutralize to a pH of 7, washed with physiological saline for 15 hours, homogenized, and potted.

[0147] Example 12

[0148] The ferritin used in this example is modified human ferritin (human light chain ferritin, LFn), which contains 24 subunits, and the amino acid sequence of each subunit is shown in SEQ ID NO:1.

[0149] 20 mg of collagen (Col, dry porcine collagen) was added to a 200 mg / mL LFn solution with a pH value of 8, and gradually stirred and dissolved in a 60°C constant temperature water bath. BDDE was added to the mixed solution of LFn and Col at a volume percentage of 6%. After stirring evenly, it was placed in a 60°C constant temperature water bath for reaction for 1.5 to 2 hours to obtain a gel of LFn chemically cross-linked Col, hereinafter referred to as LFn-Col. The gel was then washed with 0.5% HAC to neutralize to a pH of 7, washed with physiological saline for 15 hours, homogenized, and potted.

[0150] Example 13

[0151] The ferritin used in this example is modified human ferritin (human heavy chain ferritin, HFn), which contains 24 subunits, and the amino acid sequence of each subunit is shown in SEQ ID NO:2.

[0152] 20 mg of collagen (Col, dry porcine collagen) was added to a 200 mg / mL HFn solution with a pH value of 8, and gradually stirred and dissolved in a 60°C constant temperature water bath. BDDE was added to the mixed solution of HFn and Col at a volume percentage of 6%. After stirring evenly, it was placed in a 60°C constant temperature water bath for reaction for 1.5 to 2 hours to obtain a HFn chemically cross-linked Col gel, hereinafter referred to as HFn-Col. The gel was then washed with 0.5% HAC to neutralize to a pH of 7, washed with physiological saline for 15 hours, homogenized, and potted.

[0153] Embodiment 14

[0154] The ferritin used in this example is modified human ferritin (human heavy chain ferritin, HFn), which contains 8 heavy chain subunits (hereinafter referred to as HFn-8mer), and the amino acid sequence of each subunit is shown in SEQ ID NO:6.

[0155] According to the same method as in Example 1, a chemically cross-linked HFn-8mer hydrogel was prepared under neutral conditions.

[0156] Embodiment 15

[0157] The ferritin used in this example is modified human ferritin (human heavy chain ferritin, HFn), which contains 16 heavy chain subunits (hereinafter referred to as HFn-16mer), and the amino acid sequence of each subunit is shown in SEQ ID NO:7.

[0158] According to the same method as in Example 1, a chemically cross-linked HFn-16mer hydrogel was prepared under neutral conditions.

[0159] Comparative Example 1

[0160] Referring to the method of Example 1, chemically cross-linked LFn hydrogel (alkaline cross-linking) was prepared under alkaline conditions of pH 12 (200 mg / mL LFn was dissolved in NaOH to obtain a premixed solution with a pH of 12).

[0161] Comparative Example 2

[0162] Referring to the method of Example 1, chemically cross-linked HFn hydrogel (alkaline cross-linking) was prepared under alkaline conditions of pH 12 (200 mg / mL HFn was dissolved in NaOH to obtain a premixed solution with a pH of 12).

[0163] Comparative Example 3

[0164] 100 mg HA was dissolved in 1 mL of 75 mM NaOH and mixed to obtain a premixed solution with a pH value of 12. BDDE was then added to the premixed solution at a volume percentage of 6%, mixed and placed in a constant temperature water bath, the reaction temperature was set to 45 ° C, and the reaction time was 5 h to obtain a chemically cross-linked HA gel. The chemically cross-linked HA gel was then washed with 0.05 M acetic acid to a pH of 7, washed with physiological saline for 24 h, homogenized, and encapsulated to obtain a chemically cross-linked HA alkaline hydrogel.

[0165] Comparative Example 4

[0166] 100 mg of Col was dissolved in 1 mL of 0.25 M NaOH at 60 ° C by heating, and mixed evenly to obtain a premixed solution with a pH value of 12. Then BDDE was added to the premixed solution at a volume percentage of 6%, mixed evenly, and placed in a constant temperature water bath, and the reaction temperature was set to 60 ° C, and the reaction time was 5-12 hours to obtain a chemically cross-linked Col protein gel. Then the chemically cross-linked Col protein gel was neutralized to a pH of 7 by immersion in 0.05 M acetic acid, washed with physiological saline for 24 hours, homogenized, and potted to obtain a chemically cross-linked Col alkaline hydrogel.

[0167] Effect Example 1 Test Characterization Results

[0168] The hydrogels obtained in each embodiment and comparative example were characterized as follows:

[0169] 1. Microscopic morphology measurement

[0170] (1) The microstructures of the hydrogels of Examples 1-2 and Comparative Examples 1-4 were observed using a field emission scanning electron microscope.

[0171] (2) The hydrogels of Examples 1 and 10-15 were diluted 100 times and observed using a field emission transmission electron microscope.

[0172] 2. Determination of anti-enzymatic ability

[0173] (1) Uncross-linked LFn, HFn, Col and bovine serum albumin (BSA) were incubated with trypsin (trypsin) and collagenase (collagenase) at 25°C for 2 h and 24 h, respectively, and the anti-enzyme effect was detected by SDS-PAGE.

[0174] (2) For the hydrogels (LFn, HFn) and commercial HA fillers (Runbaiyan) of Examples 1-2 Black Gold), commercial Col filler (Helani ) and the hydrogels of Examples 10-13 (LFn-HA, HFn-HA, LFn-Col and HFn-Col) were measured for degradation rate according to the following steps:

[0175] Weigh a certain mass of sample and record it as m0. Put the sample into EP tubes, add 1mL of different enzyme solutions (trypsin, collagenase) to each tube, and place it in a constant temperature oscillator at 37℃ and 100r / min for different time periods, then place it in a centrifuge at 8000rpm for 5min and discard the supernatant. Dry the solution and record the mass after enzymolysis m d The sample degradation rate calculation formula is: D = (m0 – m d ) / m0×100%.

[0176] 3. Thermal stability determination

[0177] The hydrogels of Examples 1, 2, and 14-15 were incubated in pure water at 37° C., 60° C., 80° C., and 100° C. for 30 min, respectively, and then placed in a centrifuge at 8000 rpm for 5 min to observe the precipitation of the samples.

[0178] 4. Determination of swelling degree

[0179] For the hydrogels of Examples 1-2 and Comparative Examples 3-4, the mass of the dried material was measured and recorded as m0. The material was immersed in 2 mL PBS at 37°C for 24 h, and the PBS was removed after the swelling equilibrium was reached. The gel was placed on a 45° inclined plane for 1 min and then the mass was measured and recorded as m S . Swelling degree calculation formula: S = (m S -m0) / m0×100%.

[0180] 5. Determination of elastic and viscous modulus

[0181] For the hydrogels of Examples 1-2 and Comparative Examples 3-4, the viscoelasticity of the gels was measured using a Haake RS6000 (Thermo Fisher Scientific (China) Co., Ltd.) advanced rotational rheometer. Under the conditions of a test temperature of 25° C., a slit width of 1 mm, and a vibration frequency in the range of 0.1-100 Hz, the elasticity and viscosity of the hydrogels were dynamically measured, and the observation indicators were the elastic modulus (G') and the viscous modulus (G").

[0182] 6. Observation of Subcutaneous Retention Time and Retention Efficiency in Vivo

[0183] For the hydrogels of Examples 1-2 and Comparative Examples 3-4, female nude mice, 8-10 weeks old, were subcutaneously injected with each hydrogel at two points in the middle of the back of the mice, 200 μL at each point, and the volume of the gel spots was measured every 7 days for 30 days. After 30 days, the mice were killed and the remaining gel spots were dissected out and weighed.

[0184] 7. Observation of filling position movement in vivo

[0185] For the hydrogels of Examples 1-2 and Comparative Examples 3-4, female nude mice aged 8-10 weeks were selected and each hydrogel was subcutaneously injected into two points in the middle of the back of the mice, 200 μL at each point, and the displacement distance of the gel point was measured every 7 days within 30 days.

[0186] 8. In vivo inflammatory response observation

[0187] For the hydrogels of Examples 1-2 and Comparative Examples 3-4, Balb / c mice, 8-10 weeks old, were subcutaneously injected with each hydrogel at two points on the back of the mice, 200 μL at each point, and the mice were killed 48 hours later. Multifactor detection was used to detect local tissue inflammatory factors, and mice that were not subcutaneously injected (Normal) were used as blank controls.

[0188] 9. Based on the clinician's injection experience score

[0189] The hydrogels of Examples 1 and 3-9 were evaluated for injectability by 5 dermatologists. ) as control.

[0190] The results are as follows:

[0191] In the following results, each hydrogel was prepared by the previous method, and the actual application concentration was only 100 mg / mL during subcutaneous injection.

[0192] 1. Appearance and micromorphology characterization results

[0193] The cross-linked sample containing HFn was brown in color because it had ferroxidase activity and might be involved in iron metabolism in vivo as a filling material.

[0194] The microscopic morphology of the hydrogels of Examples 1-2 and Comparative Examples 1-4 is as follows: Figure 1-2 As shown, the results show that after cross-linking under neutral conditions, LFn or HFn is in a dense state, and after cross-linking under alkaline conditions, it is the cross-linking product of the monomers after depolymerization, and there is a porous structure.

[0195] The microscopic morphology of the hydrogels of Example 1 and Examples 10-15 after dilution 100 times is as follows: Figure 3 As shown. The results show that the wild-type LFn-24mer (ie, Example 1) is a complete cage structure; HFn-8mer (Example 14) is a half-bowl structure, not a cage structure; HFn-16mer (Example 15) is a cage structure of two half-bowls docked together. Furthermore, LFn-HA, LFn-Col, HFn-HA, and HFn-Col in Examples 10-13 are all cage structures, indicating that when LFn or HFn further cross-links HA or Col, the original cage structure is not affected.

[0196] 2. Characterization results of anti-enzymatic ability

[0197] The anti-enzymatic ability of uncross-linked LFn, HFn, Col and bovine serum albumin (BSA) is as follows Figure 4 The results of SDS-PAGE showed that collagenase can only decompose collagen in a targeted manner, and has no obvious degradation effect on uncross-linked LFn, HFn and BSA; under the catalysis of trypsin for 2-24h, the degradation of uncross-linked LFn and HFn is not obvious; it shows that uncross-linked LFn and HFn have the ability to resist collagenase and trypsin degradation.

[0198] The hydrogels (LFn, HFn) of Examples 1-2, commercial HA fillers (Runbaiyan Black gold), commercial Col filler (Helanni ) and the enzymatic degradation rate results of the hydrogels (LFn-HA, HFn-HA, LFn-Col, and HFn-Col) of Examples 10-13 at 37 °C are as Figure 5 shown. The results show that the degradation rates of LFn and HFn are significantly lower under the action of trypsin and collagenase; while commercial HA and commercial Co1 can be degraded by trypsin and collagenase in almost 2 h at 37 °C.

[0199] 3. Results of thermal stability measurement

[0200] Upon observation, after the hydrogels of Examples 1, 2, and 14-15 were tested at 80 °C, there were significantly more protein precipitates after the tests of the hydrogels of HFn-8mer (Example 14) and HFn-16mer (Example 15). It shows that due to structural problems, the thermal stability of the hydrogels of HFn-8mer and HFn-16mer is relatively poor.

[0201] 4. Results of swelling level and swelling degree measurement

[0202] The swelling level results of the hydrogels of Examples 1-2 and Comparative Examples 3-4 are as Figure 6 shown. The results show that swelling occurred to varying degrees after soaking. The higher the crosslinking degree, the lower the water absorption. Visually, HA swelled to a greater extent, Col swelled slightly, and LFn and HFn did not swell significantly, indicating that the crosslinking degrees of LFn and HFn are relatively high. The swelling level is LFn, HFn < Col < HA. If the swelling degree of the hydrogel is too high under physiological conditions, it will cause a decrease in the mechanical strength of the hydrogel, and may also affect the growth of surrounding tissues or cause abnormalities in body indicators.

[0203] The swelling degree results of the hydrogels of Examples 1-2 and Comparative Examples 3-4 are as Figure 7 shown. The results show that there is no significant difference in the swelling degrees of LFn (527.1%) and HFn (469.7%) compared with Col (608.7%), but they are significantly lower than HA (4756.2%), suggesting that the mechanical strengths of LFn and HFn are close to Col and higher than HA.

[0204] 5. Results of elastic and viscous modulus measurement

[0205] The elastic modulus and viscous modulus of the hydrogels of Examples 1-2 and Comparative Examples 3-4 were detected, and the results are as Figure 8As shown. G' represents the elastic modulus, G" represents the viscous modulus, and G'>G", indicating that the sample is in liquid state. After the sample is stabilized, the elastic modulus LFn is higher than 1000Pa, Col is higher than 600Pa, while HFn and HA are both lower than 200Pa; the viscous modulus LFn is higher than 100Pa, Col is higher than 30Pa, while HFn and HA are both lower than 20Pa. Both elasticity and viscosity are LFn>Col>HFn, HA, indicating that LFn has the best elasticity and viscosity, and HFn is close to HA.

[0206] 6. Observation results of in vivo subcutaneous retention time and filling position migration

[0207] For the hydrogels of Examples 1-2 and Comparative Examples 3-4, the in vivo epidermal degradation level (retention capacity / extension area) and displacement level were as follows: Fig. 9 The hydrogel was subcutaneously injected into two points in the middle of the mouse back, 200 μL at each point, and the length, width, height, and displacement (such as Fig.10 The results showed that the ferritin retention capacity of the dorsal mid-section was higher than that of HA and Col. The remaining gel spot volume LFn (1.12 cm 3 ) and HFn(0.95cm 3 ) is similar, while HA and Col are degraded to 0.34 cm 3 and 0.47cm 3 The middle back was relatively weak in mobility. Within 28 days, the subcutaneous displacement of ferritin and HA (6.38 mm) was at a similar level, significantly lower than Col 9.30 mm. Among them, the displacement of LFn was relatively the smallest (3.98 mm) (e.g. Fig.10 ).

[0208] 7. In vivo retention efficiency observation results

[0209] For the hydrogels of Examples 1-2 and Comparative Examples 3-4, the results of the mouse subcutaneous hydrogel retention experiment are as follows: Fig.11 As shown, the left picture is the result after 30 days. The results show that within one month, LFn and HFn glue points are stably retained without obvious degradation. After 30 days, Col and HA are obviously degraded, among which HA has the most obvious degradation effect. LFn and HFn are better retained than HA and Col.

[0210] 8. In vivo inflammatory response observation results

[0211] For the hydrogels of Examples 1-2 and Comparative Examples 3-4, the inflammatory factors of the subcutaneous hydrogels in mice were detected. Fig.12As shown. 48h after subcutaneous injection of Balb / c mice, serum was collected to measure inflammatory factors; inflammatory factors were measured by homogenate of gel point skin tissue. Compared with the Normal group, subcutaneous filling of LFn and HFn did not cause upregulation of inflammatory factors IL-6 and TNF-α in serum, and subcutaneous filling of LFn did not cause upregulation of inflammatory factors IL-6 and TNF-α in skin tissue, indicating that LFn does not induce inflammatory response in the body. IL-6 in serum and skin tissue was upregulated by 11.1 times and 21.2 times after HA injection.

[0212] 9. Based on the clinician's injection experience score results

[0213] The hydrogels of Examples 1 and 3-9 and Juvederm Facial Enhancement ( The injection experience scores of ) are shown in Tables 2 and 3. The meaning of each score is:

[0214] “+” means: the injection can be steadily delivered under a certain force, the needle may be slightly clogged or stuck occasionally, and the material has a certain viscoelasticity.

[0215] “++” means: the injection is smooth, there is basically no blockage or jamming, and the viscoelasticity of the material is acceptable.

[0216] “+++” means: easy to push without resistance, not easy to clog the needle, and the material has good viscoelasticity.

[0217] Table 2

[0218]

[0219]

[0220] Table 3

[0221]

[0222] The results showed that in LFn hydrogel, as the protein concentration increased, the viscosity of the hydrogel became better; in LFn hydrogel, as the volume ratio of BDDE increased, the viscosity of the hydrogel became better.

Claims

1. A modified ferritin, characterized in that It comprises a plurality of light chain subunits or heavy chain subunits of ferritin from natural sources; wherein the plurality of light chain subunits or the plurality of heavy chain subunits form a multimer, preferably a cage-shaped multimer.

2. The modified ferritin according to claim 1, characterized in that The amino acid sequence of the light chain subunit is as shown in SEQ ID NO: 1 or has at least 80% identity with the sequence shown in SEQ ID NO: 1, and the amino acid sequence of the heavy chain subunit is as shown in SEQ ID NO: 2, 6 or 7 or has at least 80% identity with the sequence shown in SEQ ID NO: 2, 6 or 7; Preferably, the modified ferritin comprises 8, 16, 24 or 48 light chain subunits or 8, 16, 24 or 48 heavy chain subunits; and / or, the natural source comprises animal, plant, fungal or bacterial sources, preferably animal sources; the animal is a vertebrate, preferably a mammal, more preferably a human; More preferably, the modified ferritin is a cage-shaped polymer composed of 24 light chain subunits, or a cage-shaped polymer composed of 24 heavy chain subunits.

3. A cross-linked ferritin, characterized in that It is a cross-linked ferritin formed by cross-linking of ferritin from a natural source or a variant thereof, and the cross-linked ferritin retains the polymer structure of the ferritin from a natural source or a variant thereof; or it is a cross-linked ferritin formed by cross-linking of the modified ferritin according to claim 1 or 2, and the cross-linked ferritin retains the polymer structure of the modified ferritin; wherein the variant has at least 80% identity with the amino acid sequence of the ferritin from a natural source; Preferably, the cross-linked ferritin is in the form of a hydrogel or microsphere structure.

4. The cross-linked ferritin according to claim 3, characterized in that The swelling degree of the cross-linked ferritin is less than 1000%, preferably less than 600%, more preferably less than 500%; and / or, the elastic modulus of the cross-linked ferritin is higher than 100 Pa, preferably higher than 600 Pa, more preferably higher than 1000 Pa; and / or, the viscosity modulus of the cross-linked ferritin is higher than 10 Pa, preferably higher than 30 Pa, more preferably higher than 50 Pa, and even more preferably higher than 100 Pa; And / or, the natural source includes animal, plant, fungal or bacterial sources, preferably animal sources; the animal is a vertebrate, preferably a mammal, and more preferably a human; Preferably, the cross-linking is performed by a biological cross-linking reaction or a chemical cross-linking reaction.

5. The cross-linked ferritin according to claim 3, characterized in that The cross-linked ferritin further comprises hyaluronic acid and / or collagen; Preferably, the volume ratio of the cross-linked ferritin to the hyaluronic acid is 1:5-5:1; or, the volume ratio of the cross-linked ferritin to the collagen is 1:5-5:1; Or, the molar concentration ratio or mass ratio of the cross-linked ferritin to the hyaluronic acid is 1:5-5:1; or, the molar concentration ratio or mass ratio of the cross-linked ferritin to the collagen is 1:5-5:

1.

6. A method for preparing cross-linked ferritin as claimed in any one of claims 3 to 5, characterized in that: The method comprises the following steps: The naturally derived ferritin or its variant, or the modified ferritin as claimed in claim 1 or 2, is made into cross-linked ferritin through a cross-linking reaction; the cross-linking reaction is a chemical cross-linking reaction or a biological cross-linking reaction.

7. The method according to claim 6, characterized in that When the cross-linking reaction is a chemical cross-linking reaction, the cross-linking reaction comprises the following steps: A neutral solution containing ferritin from natural sources or its variants, or a neutral solution containing the modified ferritin as claimed in claim 1 or 2, is mixed with a cross-linking agent to carry out a cross-linking reaction to obtain the product; And / or, after the cross-linking reaction, the step further includes mixing hyaluronic acid and / or collagen into the cross-linked ferritin; And / or, after the cross-linking reaction, neutralization, washing and / or homogenization are further included; When the cross-linking reaction is a biological cross-linking reaction, the natural ferritin is cross-linked via disulfide bonds; preferably, the natural ferritin is fused and expressed with a cysteine-containing polypeptide by genetic engineering to obtain cross-linked ferritin; Preferably, the natural source includes animal, plant, fungal or bacterial sources, preferably animal sources; the animal is a vertebrate, preferably a mammal, and more preferably a human.

8. The method according to claim 7, characterized in that When the cross-linking reaction is a chemical cross-linking reaction, the method comprises one or more of the following conditions: ① The cross-linking agent is selected from one or more of 1,4-butanediol diglycidyl ether, genipin, 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride, N-hydroxysuccinimide, nordihydroguaiaretic acid and glutaraldehyde, preferably 1,4-butanediol diglycidyl ether; ② The volume percentage of the cross-linking agent relative to the neutral solution is 3-30%, preferably 6%; ③ The cross-linking reaction is carried out in a constant temperature water bath; the temperature of the cross-linking reaction is preferably 60-72°C, more preferably 60°C; the time of the cross-linking reaction is preferably 20-150min; ④ The pH of the neutral solution is 8; ⑤ The concentration of the naturally derived ferritin or its variant, or the modified ferritin as described in claim 1 or 2 is 10-600 mg / mL, preferably 50-300 mg / mL, for example 100 mg / mL.

9. The method according to claim 7 or 8, characterized in that The method includes one or more of the following conditions: ① The neutralization includes pickling to neutrality; the pickling preferably includes leaching with an acidic agent; preferably, the acidic agent is selected from one or more of hydrochloric acid, sulfuric acid and acetic acid, more preferably acetic acid; ② The cleaning includes cleaning with a buffered saline solution; preferably, the buffered saline solution is selected from one or more of phosphate buffer, saline, Tris-HCl buffer and HEPES; and or, the concentration of the buffered saline solution is 10-100 mM and the pH is 6-8; ③The cleaning time is 12-30h.

10. Use of ferritin from natural sources or its variants, or the modified ferritin as claimed in claim 1 or 2, in the preparation of a subcutaneous or tissue filler; wherein: The variant has at least 80% identity with the amino acid sequence of ferritin from natural sources; Preferably, the natural source includes animal, plant, fungal or bacterial sources, preferably animal sources; the animal is a vertebrate, preferably a mammal, and more preferably a human.

Citation Information

Patent Citations

  • Voltage compensating method of serially connected electrically energy quality compensator

    CN1134094C